2003
DOI: 10.1093/humrep/deg369
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twinning following assisted conception: an analysis of 81 consecutive cases

Abstract: The risk of monoamniotic twinning is increased following IVF/embryo transfer. Zona pellucida disruption appears to increase the incidence of MZ twinning. However, the overall micromanipulation data together with the unexpected placentation data suggest that zona-mediated embryo splitting is not the only mechanism of twinning under artificial conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 32 publications
6
101
0
4
Order By: Relevance
“…Therefore, we are probably seeing only the tip of an iceberg. MC DZT cannot totally be ruled out in some previously reported DZT who were the outcome of pregnancy by IVF because not enough information for their placental nature was given Steinman et al 2003;Alikani et al 2003) . Furthermore, some twins collected in a large survey for ART-associated MZT might be the case, as MZT twinning has been observed in such a series for more than one fetus in the same gestational (MC) sac .…”
Section: Future Perspectivesmentioning
confidence: 98%
“…Therefore, we are probably seeing only the tip of an iceberg. MC DZT cannot totally be ruled out in some previously reported DZT who were the outcome of pregnancy by IVF because not enough information for their placental nature was given Steinman et al 2003;Alikani et al 2003) . Furthermore, some twins collected in a large survey for ART-associated MZT might be the case, as MZT twinning has been observed in such a series for more than one fetus in the same gestational (MC) sac .…”
Section: Future Perspectivesmentioning
confidence: 98%
“…They found that the rate of multiple pregnancies (10.8% vs. 2.6%) and monozygotic twinning (5.9% vs. 0) was increased in the ICSI group compared to the conventional IVF group (P = 0.039 and P = 0.033, respectively). Alikani et al [4] reviewed all IVF cycles in their program over the preceding seven years that resulted in a positive fetal heart at 6 weeks gestational age and showed an overall rate of monozygotic twinning of 1.88%. In examining the role of ICSI they reported a rate of monozygotic twinning of 2.35% (31/1537) with ICSI and 1.58% (35/2185) with standard insemination.…”
Section: Discussionmentioning
confidence: 99%
“…20 ). Zona hardening may squeeze the inner cell mass (icm) and induce embryo splitting during hatching 24 . increased mZT might also correlate with the transfer of high-quality embryos, which are more often transferred after prolonged culture.…”
Section: Length Of Culturementioning
confidence: 99%